Impact of an interatrial shunt device on survival and heart failure hospitalization in patients with preserved ejection fraction. (11th October 2018) - Kaye, David M.; Petrie, Mark C.; McKenzie, Scott; Hasenfuβ, Gerd; Malek, Filip; Post, Martijn; Doughty, Robert N.; Trochu, Jean‐Noël; Gustafsson, Finn; Lang, Irene; Kolodziej, Adam; Westenfeld, Ralf; et al.
Abstract: Aims: Impaired left ventricular diastolic function leading to elevated left atrial pressures, particularly during exertion, is a key driver of symptoms and outcomes in heart failure with preserved ejection fraction (HFpEF). Insertion of an interatrial shunt device (IASD) to reduce left atrial pressure in HFpEF has been shown to be associated with short‐term haemodynamic and symptomatic benefit. We aimed to investigate the potential effects of IASD placement on HFpEF survival and heart failure hospitalization (HFH). Methods and results: Heart failure with preserved ejection fraction patients participating in the Reduce Elevated Left Atrial Pressure in Patients with Heart Failure study (Corvia Medical) of an IASD were followed for a median duration of 739 days. The theoretical impact of IASD implantation on HFpEF mortality was investigated by comparing the observed survival of the study cohort with the survival predicted from baseline data using the Meta‐analysis Global Group in Chronic Heart Failure heart failure risk survival score. Baseline and post‐IASD implant parameters associated with HFH were also investigated. Based upon the individual baseline demographic and cardiovascular profile of the study cohort, the Meta‐analysis Global Group in Chronic Heart Failure score‐predicted mortality was 10.2/100 pt years. The observed mortality rate of the IASD‐treated cohort was 3.4/100 pt years, representing a 33% lower rate ( P = 0.02). By Kaplan–Meier analysis, the observed survival in IASD patients was greater than predicted ( P = 0.014). Baseline parameters were not predictive of future HFH events; however, poorer exercise tolerance and a higher workload‐corrected exercise pulmonary capillary wedge pressure at the 6 months post‐IASD study were associated with HFH. Conclusions: The current study suggests IASD implantation may be associated with a reduction in mortality in HFpEF. Large‐scale ongoing randomized studies are required to confirm the potential benefit of this therapy.